Pengaruh Strengthening Exercise Terhadap Nyeri Leher Akibat Spasme Otot Upper Trapezius Pada Tenaga Kesehatan Di Rs Toeloengredjo Pare Kediri - Dewi Retno Wulandari; Yohanes Deo Fau; Amin Zakaria; Agung Hadi Endaryanto (Jurnal Keperawatan Muhammadiyah, 2023)
Objective : To analyze the effect of giving strengthening exercise to neck pain due to spasm of the upper trapezius muscle in the contra lateral area in health workers at Toeloengredjo Hospital Pare KediriMethods : This article uses pre and post test trials conducted on 20 health workers who experience neck pain due to upper trapezius spasm. This strengthening exercise was carried out for 4 weekswith an intensity of 8 meetings (2 times a week).Results: Strengthening exercise in the first and second weeks had no significant effect on reducing neck pain with a significant value effec on reducing neck pain with a significant value with asymp. sig. 2-tailed 1.00 > 0.05. While weeks 3 and 4 experienced a decrease in pain with the value of the 3 week asymp. sig. 2-tailed value 0.025<0.05 and 0.000<0.05 at week 4.Conclusion: Strengthening exercise have an effect on reducing neck pain due to spasem of the upper trapezius contalateral area in internal health workers training health workers training period of more than 1 week (minumum 2 weeks to 4 weeks / 1 month). The average reduction in pain in 20 health workers after Â² weeks was seen from the Wilcoxon Signed Rank test with an asymp value. sig. 2-tailed worth 0.000<0.05.